Mechanism of antiphospholipid antibody-mediated thrombosis in antiphospholipid syndrome - Yang, Leiyi; Guo, Ruibing; Liu, Hongjiang; Chen, Bo; Li, Changpei; Liu, Ruiting; Liao, Shuyi; Xie, Qibing; Yin, Geng (Frontiers in Immunology, 2025)
Antiphospholipid syndrome (APS) is an autoimmune disease characterized by the occurrence of thrombotic or obstetrical events in patients with persistent antiphospholipid antibodies (aPL). Thrombotic events, the primary pathological hallmarks and clinical manifestations, are among the leading causes of mortality in APS. Our understanding of the mechanism underlying APS-related thrombosis has significantly advanced in recent years. The presence of aPL, particularly anti-β2-glycoprotein I (anti-β2GPI) antibodies, is a major driver of thrombosis. The proposed pathophysiological mechanisms of aPL-mediated pro-thrombotic events can be broadly categorized into three types: disruption of anticoagulant reactions and fibrinolysis, interference with coagulation cascade cells, and complement activation. A triggering ‘second hit’ is typically necessary to initiate thrombosis. The development of animal models of APS has further refined our understanding of the role of aPL in thrombosis. In this review, we focused on the role of β2GPI-dependent aPL in thrombosis of thrombotic APS.